2023
DOI: 10.11591/ijere.v12i1.23390
|View full text |Cite
|
Sign up to set email alerts
|

Distance learning during COVID-19 pandemic: A study of Moroccan university students

Abstract: Because of COVID-19, distance learning was adopted by the majority of educational institutions as a strategy to ensure the continuity of education. In Morocco, forcing students to change their traditional learning methods has put them through an unprecedented learning experience. This study aims at investigating Moroccan university students of English experiences with distance learning during the pandemic in terms of readiness, satisfaction and perceived barriers. To achieve the objectives of the study, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The two categories II and IV (14%) are complementary to each other, as both indicate that contact between students helps reduce feelings of isolation. This result is in line with data from our literature search, where several researchers [20][21][22][23] have highlighted that distance learning can create a sense of isolation among learners. For category III, respondents chose face-to-face teaching because of its effectiveness in assessing students' knowledge.…”
Section: B) Preference For Face-to-face Teachingsupporting
confidence: 91%
See 1 more Smart Citation
“…The two categories II and IV (14%) are complementary to each other, as both indicate that contact between students helps reduce feelings of isolation. This result is in line with data from our literature search, where several researchers [20][21][22][23] have highlighted that distance learning can create a sense of isolation among learners. For category III, respondents chose face-to-face teaching because of its effectiveness in assessing students' knowledge.…”
Section: B) Preference For Face-to-face Teachingsupporting
confidence: 91%
“…This teaching and learning modality preserves interaction between students and teacher. It minimizes the disadvantages generally associated with online courses, such as lack of support, feelings of isolation and reduced interaction [20][21][22][23]. As a result, many authors identify hybrid courses as an alternative for increasing student engagement and thus improving learning quality [24][25][26][27][28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the educational institutions have turned to e-learning platforms to pursue their learning goals [4], [5]. The COVID-19 epidemic has compelled governments, corporations, and other organizations in addition to colleges to organizations to rapidly scale their electronic service offerings [6], [7]. Most tertiary organizations, especially in Indonesia, had to introduce and utilization of online technology in emergency distance learning to maintain learning activities during the novel coronavirus pandemic [8].…”
Section: Introductionmentioning
confidence: 99%
“…Further, since the COVID-19 outbreak, educational challenges have increased, leading to the adoption of distance learning. Studies indicated that distance-learning students have a moderate level of readiness engagement, are less satisfied with this learning method, prefer classroom instruction, and have issues interacting with lecturers and peers [20]. These changes, challenges, and obstacles can affect the success of higher education completion.…”
Section: Introductionmentioning
confidence: 99%